The influence of stacking sequence on the low-velocity impact response and damping behavior of carbon and flax fabric reinforced hybrid composites - Anni Wang (Elsevier, 2021)
With the wide application of fiber reinforced polymer (FRP) composites, the impact resistance and damping properties of FRP have been considered as the essential properties of many applications. In this paper, the hybrid composites (FCFCF, where C represents carbon fiber layer and f represents flax layer) and sandwich structure (CFFFC) alternately laminated with carbon fiber and flax fabric were studied by vacuum-assisted resin pouring (VARI) process, and the effects of stacking sequence of carbon fiber and flax fabric layers on low-speed impact response and damping properties were studied. The better impact response and higher energy absorption of hybrid composites with the sandwich structure are attributed to the higher strength of the skin layer and better adhesion between core layers. Furthermore, affected by the types of surface fibers, FCFCF has lower vibration frequency and higher energy consumption, and its damping coefficient is 26.4% higher than that of CFFFC.